Current Perspective Concerning the Potential Value of Chloroplast Lipidome in Assessing Moss Response to Abiotic Stress During Boreal Forest Regeneration - Callahan, Grace; Zhu, Xinbiao; Thomas, Raymond H. (Frontiers in Forests and Global Change, 2022)
Mosses play important roles in the regulation of environmental or metabolic conditions in boreal forest ecosystems. Sphagnum and feathermoss are the two main bryophytes found in boreal forest understory. Clearcut harvesting (common method of boreal forest regeneration) can expose understory vegetation to water and light stress. Water and light stress can significantly impact moss growth during boreal forest regeneration. Analysis of the membrane lipidome, photosynthetic parameters and pigments can be very effective in assessing moss response to abiotic stress following clearcut harvesting. Although lipidomics is commonly used in environmental stress assessment of plants, application to assess moss lipidome and stress response is very limited. Bryophytes may alter or remodel their membrane lipid composition to acclimate or adapt to environmental stressors. Thus, this perspective provides insights into how moss lipids may serve as useful biomarkers of moss stress response or adaptation to environmental stress during boreal forest regeneration following clearcut harvesting.